2017
DOI: 10.1016/j.ijsu.2017.02.058
|View full text |Cite
|
Sign up to set email alerts
|

Anterior corpectomy comparing to posterior decompression surgery for the treatment of multi-level ossification of posterior longitudinal ligament: A meta-analysis

Abstract: This meta-analysis indicates that the parameters of outcomes and functional recovery of patients performed with anterior surgery achieve better JOA scores and recovery rates to those with posterior surgery. Though the incidence of complications of anterior surgery are higher than posterior surgery, the anterior directly decompression is advised when the complications could be controlled by advanced surgical technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 11 publications
3
16
0
Order By: Relevance
“…Cervical OPLL results from pathologic replacement of cervical posterior longitudinal ligament with lamellar bone. [ 20 ] OPLL cause spinal cord compression and neurologic deterioration including changes in gait or balance, loss of fine motor control, and upper extremity weakness, numbness, or paresthesias. [ 9 ] Patients with cervical OPLL are at an increased risk of acute spinal cord injury with trauma and rapid neurologic deterioration in association with even a minor trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical OPLL results from pathologic replacement of cervical posterior longitudinal ligament with lamellar bone. [ 20 ] OPLL cause spinal cord compression and neurologic deterioration including changes in gait or balance, loss of fine motor control, and upper extremity weakness, numbness, or paresthesias. [ 9 ] Patients with cervical OPLL are at an increased risk of acute spinal cord injury with trauma and rapid neurologic deterioration in association with even a minor trauma.…”
Section: Discussionmentioning
confidence: 99%
“…The posterior procedure is relatively simple and with low complication rates, and it has been widely used as an initial surgery for cervical OPLL [ 15 ]. Though the results of the posterior surgery depend on the backward shift of the cervical spinal cord [ 5 ], it has been shown to have the same excellent results as anterior decompression surgery [ 19 , 20 ]. Relief of symptoms or prevention of symptom progression has been achieved in most patients after surgical decompression of cervical OPLL.…”
Section: Discussionmentioning
confidence: 99%
“…When considering revision surgery for patients who have already received posterior decompression surgery, it is impossible to again perform decompression from the posterior aspect. Anterior cervical corpectomy and fusion may be a good choice; however, it is considered technically demanding and is associated with serious complications, such as intraoperative spinal cord injury, symptomatic CSF leakage, adjacent segment disease, and graft dislodgment [ 5 ]. Macdonald et al reported that multilevel anterior cervical corpectomy and fusion carries an approximately 22% risk of surgical mortality and morbidity, including pneumonia, deep vein thrombosis, and death [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Surgical procedures for cervical OPLL include posterior decompression with laminectomy or laminoplasty, posterior decompression with instrumented fusion, and anterior decompression and fusion surgeries. 3 Anterior procedures include both extirpation and floating of the ossification foci according to the surgeon's decision. Massive ossification foci often show tight adhesion to the dura mater, resulting in difficulty in extirpation without a dural injury or dural defect.…”
Section: Introductionmentioning
confidence: 99%